Steps Towards a Conceptualisation of Digital Institutions of Knowledge. (March 2013) - Madsen, Anders Koed
Digital traces are increasingly used as data with which to generate insights into social dynamics around complex issues such as the controversies surrounding biotechnology. Hyperlinks can, for example, be used to locate a network of relevant stakeholders around an emerging technology and a popular way to makes sense of this kind of data is to rely on software that can synthesise it and present it in 'Web-based visualisations'. This short article presents a discussion of ways in which such visualisations can be made an object of social scientific study and it provides tentative steps towards a theoretical framework that allows us to conceptualise such visualisations as emerging 'Digital Institutions of Knowledge'. This framework is rooted in discursive and process oriented institutionalisms and in the concept of 'market devices' which has been powerful within economic sociology. The ordinally ranked results of Google are presented as the simplest examples of a Web-based visualisation and its relevant theoretical characteristics are emphasised by juxtaposing it to FICO-scores which serve as an example of a market device. Similarities and differences between the two devices are used as a basis from which to ponder the institutional aspects of Web-based visualisations.